2019
DOI: 10.1177/1729881419834756
|View full text |Cite
|
Sign up to set email alerts
|

Typical configuration analysis of a modular reconfigurable cable-driven parallel robot

Abstract: To obtain better flexibility and multifunction in varying practical applications, several typical configurations of a modular reconfigurable cable-driven parallel robot are analyzed in this article. The spatial topology of the modular reconfigurable cable-driven parallel robot can be reconfigured by manually detaching or attaching the different number of modular branches as well as changing the connection points on the end-effector to satisfy diverse task requirements. The structure design of the modular recon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…More clearly, the possibility of manually attaching or detaching a desired number of modular branches enables to adjust their spatial topology as required, where modifying the connection points on the End-Effector allows for applicability to a further diversified spectrum of RAD-related operations. The vector closed rule and the Lagrange method constitute essential elements in analyzing, understanding and solving the underlying Inverse Kinematic Problem 11 using Inverse Dynamic Programming 12 , which is a prerequisite for making use of the robot in an effective and efficient way [75].…”
Section: A Types Of Robotsmentioning
confidence: 99%
“…More clearly, the possibility of manually attaching or detaching a desired number of modular branches enables to adjust their spatial topology as required, where modifying the connection points on the End-Effector allows for applicability to a further diversified spectrum of RAD-related operations. The vector closed rule and the Lagrange method constitute essential elements in analyzing, understanding and solving the underlying Inverse Kinematic Problem 11 using Inverse Dynamic Programming 12 , which is a prerequisite for making use of the robot in an effective and efficient way [75].…”
Section: A Types Of Robotsmentioning
confidence: 99%
“…Reconfigurable mechanisms include metamorphic mechanisms and motion bifurcation mechanisms; the difference between them is mainly whether the topological structure of the mechanism has changed. There are six basic evolutionary rules of the metamorphic mechanism: (1) the mechanism's number of limbs changes [5]; (2) the relative position of each limb and platform of the mechanism changes [6]; (3) the parameters (number, relative position, and geometric parameters) in each limb of the mechanism change [7]; (4) the parameters of the kinematic pairs (type, quantity, direction, and relative position) in each limb of the mechanism change [8]; (5) the moving platform is transformed into a non-rigid series open-loop mechanism or a closed-loop mechanism with an integrated end-effector [9]; (6) the mechanism switches between the reference and moving plane [10]. The basic evolution rule of motion of bifurcation mechanisms is to change the instantaneous freedom of the mechanism by switching different motion modes through a singular configuration.…”
Section: Introductionmentioning
confidence: 99%
“…Pott et al [23] suggested a method to determine the space taken by the cables when the robot is moving, considering that the cable trajectory takes the form of a cone. In References [24,25] the authors analyzed several typical configurations of a modular reconfigurable cable-driven parallel robot. Finally, in Reference [26] the author presented a study of the advantages of reconfigurable platforms in parallel robots and suggested a new method for dealing with the constrains in the kinematic coupling of limbs.…”
Section: Introductionmentioning
confidence: 99%